2016
DOI: 10.7754/clin.lab.2016.160615
|View full text |Cite
|
Sign up to set email alerts
|

Cell Free DNA and Procalcitonin as Early Markers of Complications in ICU Patients with Multiple Trauma and Major Surgery

Abstract: cfDNA is a good predictor of patient outcome in ICU and to a lesser extent as a marker of sepsis. PCT is another promising marker that can complement cfDNA to reach better patient management. Other markers can help in less severe cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In the liver transplantation, hematoma, CMV infection, and acute rejection led to increased ddcfDNA fractions up to 90% compared to 10% during stable graft function [6]. Infection can also lead to an increase in level of ddcfDNA, and one study reported that a combination of ddcfDNA with PCT can distinguished the infection leading to the ddcfDNA increase [20].We detected human parvovirus B19 reads in recipient p19 at the 2nd post-operative day, and the dynamic increase in B19 reads over time. At last, the recipient was confirmed with human parvovirus B19 infection with low hemoglobin and recovered after treatment with IVIG.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver transplantation, hematoma, CMV infection, and acute rejection led to increased ddcfDNA fractions up to 90% compared to 10% during stable graft function [6]. Infection can also lead to an increase in level of ddcfDNA, and one study reported that a combination of ddcfDNA with PCT can distinguished the infection leading to the ddcfDNA increase [20].We detected human parvovirus B19 reads in recipient p19 at the 2nd post-operative day, and the dynamic increase in B19 reads over time. At last, the recipient was confirmed with human parvovirus B19 infection with low hemoglobin and recovered after treatment with IVIG.…”
Section: Discussionmentioning
confidence: 99%
“…Cell‐free plasma DNA (cfDNA), also called extracellular DNA, comprises fragments of DNA that are released from apoptotic and necrotic cells . Elevated levels of cfDNA in blood have been found in various clinical conditions, such as cancer, trauma, stroke and sepsis . A few studies have indicated that cfDNA may have value in predicting the mortality of sepsis patients in intensive care units (ICUs) and in emergency department (ED) patients .…”
Section: Introductionmentioning
confidence: 99%
“…Here, i.e., cfDNA, also known as extracellular DNA, which can be released by various host cells including neutrophils, macrophages, eosinophils, and tumor cells, as well as by certain strains of bacteria plays a significant role [77][78][79][80][81][82]. Elevated levels of cfDNA have been found in various pathologic conditions including trauma [83,84]. Interestingly, cfDNA that appears to exert both pro-and antifibrinolytic effects is a good predictor of trauma patient's outcome in the ICU [84].…”
Section: Dampsmentioning
confidence: 99%
“…Meanwhile, we are beginning to understand the large impact of cfDNA on posttraumatic inflammation. Release of cfDNA plays an important role in trauma [84,256]. The group around Hauser [256] has shown that traumatic injury causes a release of mtDAMPs into the circulation, which have functionally important immune consequences.…”
Section: Nucleic Acidsmentioning
confidence: 99%